Sanitation And Hygiene Of Food Stalls In The Dehasen University Of Bengkulu - Kesuma, Ogi Wijaya; Moulina, Methatias Ayu; Nur’aini, Hesti (CV. Utami, 2025)
Hygiene and sanitation are actions or efforts to improve cleanliness and health through early maintenance of every individual and the environmental factors that influence them, so that individuals are protected from the threat of disease- causing germs. This research was conducted on eateries within a 200-meter radius of campus 1 and 2 of Universitas Dehasen Bengkulu. There are a total of 25 eateries in the vicinity of campus 1, while there are 10 eateries in the vicinity of campus 2. In total, there are 35 eateries within the university environment that were studied. This research used a descriptive quantitative method to achieve its objectives. The measurement method in this research used a dichotomous scale that only has 2 answer choices: yes and no. In calculating the data, the researcher used Guttman scale analysis. The application of sanitation in eateries is very good at 95%, but the application of hygiene is only 69%, which falls into the good category and still requires improvement and enhancement. The level of satisfaction of respondents towards the application of sanitation and hygiene in eateries at Universitas Dehasen Bengkulu environment is very good. Out of 105 respondents, the satisfaction rate is 94%.